Composting period of oil palm empty fruit bunch (EFB) suitable as substrate for Volvariella volvacea mushroom production - Ismail, Mohamad Hazim (2019)
Mushroom has been considered as a vital food resource and has been regards to have many medicinal properties that can help to boost the human health and act as alternative food resource in some area of the world. The cultivation of the mushroom has been intensive and many methods have been discovered to increase the yield of the mushroom. In Malaysia, the cultivation of V. volvacea are done using palm oil empty fruit bunch (EFB) as the substrate. The research objective is to determine the effect of composting period on V. volvacea mushroom production and determine the suitable composting condition. This research was carried out in Hutan Simpan Ayer Hitam located at Puchong, Selangor. The V. volvacea was grown on the EFB bed with respective composting period, 6, 9 and 12 day. The microclimate data was recorded during 6, 9 and 12 days composting period. Then, the mushroom yield was observed and recorded for 30 days period of harvesting. This research found that different composting period did not have significant impact on the production of mushroom in terms of weight and number of mushroom produced during harvesting. In conclusion, the composting period 6, 9 and 12 days achieved suitable condition of temperature, pH and moisture content for the microorganism to thrive and provide suitable compost for the mushroom to grow.